2017
DOI: 10.1093/geront/gnx024
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Religion and Spirituality on Cognitive Function: A Systematic Review

Abstract: Public health practitioners should not overlook the benefits of enabling religious/spiritual practices among religious adults (i.e., offering ride programs could help isolated elders attend religious gatherings).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 34 publications
5
48
0
Order By: Relevance
“…Spirituality plays an important part in many people’s lives, especially elders [48]. One systematic review found that spirituality had a protective effect on cognitive decline [49] and thus, supporting elders to engage in activities that support their spirituality, whatever spirituality they choose, could support their overall health and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Spirituality plays an important part in many people’s lives, especially elders [48]. One systematic review found that spirituality had a protective effect on cognitive decline [49] and thus, supporting elders to engage in activities that support their spirituality, whatever spirituality they choose, could support their overall health and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were too heterogeneous for a meta-analysis to be conducted. Heterogeneity between studies was observed in the varying approaches used to assess R/S, ranging from the different instruments used across studies to multiple dimensions of R/S examined; these issues have been acknowledged in prior systematic reviews [ 25 , 26 ]. We provide a qualitative synthesis of the results obtained from the studies identified in our review.…”
Section: Methodsmentioning
confidence: 99%
“…56 Nevertheless, higher levels of spirituality have been associated with a slower rate of cognitive decline in patients with AD 57 and in the healthy elderly. 58,59 Therefore, spiritual well-being could potentially work as a mediator of the MBSR effect, especially on depressive symptoms and anxiety.…”
Section: Introductionmentioning
confidence: 99%